1994
DOI: 10.1111/j.1365-2249.1994.tb06609.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating proinflammatory cytokines (IL-1β, TNF-α, and IL-6) and IL-1 receptor antagonist (IL-1Ra) in fulminant hepatic failure and acute hepatitis

Abstract: Fulminant hepatic failure (FHF) is characterized by massive necroinflammation of the liver tissue and is associated with high mortality. Serum concentrations of IL-1 beta, tumour necrosis factor-alpha (TNF-alpha), IL-6 and IL-1 receptor antagonist (IL-1Ra) were measured in 30 patients with FHF and in 23 patients with acute hepatitis (AH) before start of treatment and in 23 healthy controls. Levels of all four molecules were increased significantly in FHF compared with AH, in which values were higher than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(88 citation statements)
references
References 39 publications
6
75
0
2
Order By: Relevance
“…The balance between IL-1 and IL-1Ra seems crucial in inflammatory diseases [15][16][17][18]. Although IPF is not primarily an inflammatory disease, IPF is characterized by high levels of inflammatory parameters.…”
Section: Il-1 Receptor Antagonist In Ipfmentioning
confidence: 99%
“…The balance between IL-1 and IL-1Ra seems crucial in inflammatory diseases [15][16][17][18]. Although IPF is not primarily an inflammatory disease, IPF is characterized by high levels of inflammatory parameters.…”
Section: Il-1 Receptor Antagonist In Ipfmentioning
confidence: 99%
“…Values with a diagnostic accuracy greater than 50% had acceptable specificity but low sensitivity (Table 6). A threshold value of greater than 200 mol/L had specificity of 92% (95% CI: 88-95) but sensitivity of 25% (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), failing to identify 36 of 48 (75%) patients who developed ICH.…”
Section: Admissionmentioning
confidence: 99%
“…[8] Extensive genetic polymorphisms have also been described, which in many cases appear to play an important part in their level of expression and have been linked to a variety of diseases, [6] as a variety of experiments has shown that either excessive or insufficient production of cytokines may contribute significantly to the pathophysiology of a range of diseases [2] including hepatic diseases. [9] GENERAL PROPERTIES OF CYTOKINES Cytokines can be produced by virtually every nucleated cell type in response to injurious stimuli [ Table 2]. [10] Mostly, cytokines are produced and act locally.…”
Section: Introductionmentioning
confidence: 99%